Model Tests and FE-Modelling of Dynamic Soil-Structure Interaction - N. Kodama; K. Komiya (Shock and Vibration)
The forces applied to a structure from the soil ground during an earthquake and the dynamic response of a structure are problems that are not well understood. In recent years, seismic design technology aided by numerical simulation is under active development. Successful improvement of the accuracy and reliability of numerically simulated results relies on a clear understanding of the seismic force transmission mechanism between the soil and a structure associated with mechanical properties of soil.